Neonatal Guillain-Barre' Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
A term female infant presenting with generalized hypotonia, paucity of lower limb movements, and diminished DTRs was diagnosed as a case of Guillain-Barre' syndrome at the Hospital for Sick Children, University of Toronto, Canada.